Corporate Culture and Employee Competence Effects on Employee Performance with Organizational Commitment at Bank BXXXS Tbk - Wicaksana, Mulya; Kasmir, Kasmir (Green Publisher Indonesia, 2023)
Basically, performance is an individual thing because each individual will have a different level of performance according to the values ​​that apply to each individual. The more aspects of work that are in accordance with individual wishes, the higher the level of performance. This study aims to analyze the effect of corporate culture, employee competence, on employee performance with organizational commitment as a mediating variable. The subjects of this study were BXXXS Bank employees in the Risk Management unit, with a population of 50 people. The data collection technique uses a questionnaire instrument with a Likert scale measurement. Data were analyzed using SmartPLS software version 3.3.7. The results of this study indicate that corporate culture has an effect on employee performance variables, corporate culture has no effect on work commitment variables, employee competencies have an effect on employee performance variables, employee competencies have had an effect on corporate culture variables have no effect on employee performance through work commitment and employee competence has no effect on employee performance through work commitment.